Protective Effect of Orthosiphon stamineus Benth Leaves Extract against Reheated palm oil-induced Liver Damage in Mice - Annisah, Fitroh; Widjokongko, Bambang; Utari, Siti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Orthosiphon stamineus Benth contains polyphenols, terpenoids, oleanolat acids, and sterols which were thought to protect the liver from free radicals. In present study, Orthosiphon stamineus Benth leaves extract was evaluated for its protective effect on reheated palm oil -induced liver damage in mice. Methods: This was laboratory experimental research with the post test only controlled group design. Twenty five male Swiss webster mice were equally divided into five groups: group I (Kn) received aquadest, group II (Kp) received reheated palm oil, and grup IIIâV (P1-P3) received reheated palm oil and multilevel doses of Orthosiphon stamineus Benth leaves extract (3.5 mg, 7 mg, and 14 mg) for 14 days. Mice were sacrificed on the 15th day and histological preparation was made to evaluate histological damage on liver. Liver histological featuresÂ wereÂ assessedÂ byÂ countingÂ theÂ numberÂ of hepatocyte on centrolobuler zone undergoing pyknosis, karyorhexis, and karyolysis. Data were analyzed using the One Way ANOVA test (Î± = 0.05) and the Post Hoc Multiple Comparisons (LSD) test (Î± = 0.05). Results: The mean liver histological damage score was significantly higher on group of Kp= 74.40 Â± 2.074, while group of Kn= 38.20 Â± 3,564 as the less. P2 group had fewer numbers of liver histological damage (57.00 Â± 4.472) compared to the P1 group (61.00 Â± 2.550) and the P3 group (58.60 Â± 4.775). The results of One Way ANOVA test showed significant difference between the five groups (p = 0.000) and the results of LSD test showed significant differences between each other group (p < 0.005), except the group of P1-P2, P1-P3, and P2-P3 (p > 0.005). Conclusions: Orthosiphon stamineus Benth leaves extract showed protective effect against the hepatotoxicity induced by reheated palm oil in mice. Orthosiphon stamineus Benth leaves extract with the dose of 7 mg/25 g body weight of mice showed a higher hepatoprotective effect than the dose of 3.5 mg/25 g body weight of mice and 14 mg/25 g body weight of mice. Keywords: Orthosiphon stamineus Benth leaves extract, reheated palm oil, histologic liver damage.Â